Fome, devoração e os saberes do pé: antropofagia como possibilidade de produção de conhecimento e crítica das desigualdades contemporâneas - Santos, Rafael Renato dos (Universidade Federal de São Carlos, 2022)
The present research focuses on the notion of Anthropophagy developed by Oswald de Andrade from the Anthropophagous Manifesto and the essays, theses, articles and interviews in which he returns to the theme, during his last years of life. With regard to a definition of Anthropophagy, it is possible to verify that there are several meanings linked to it, among which we infer at least three effective connotations: ritual, cultural and philosophical Anthropophagy. It is common to observe in the writings of Oswald and other authors who discussed Anthropophagy the pretension that it could occupy a place of theoretical protagonism and that it could constitute a kind of approach capable of thinking about different aspects of Brazilian society in a critical way. In this sense, the research aims to clarify whether Oswald's claim can be carried out and, advancing in the field of philosophical Anthropophagy, verifies the possibilities of using it as an approach capable of establishing readings on contemporary events and producing knowledge that has as a foundation the critical perspective of social inequalities. The work is based on bibliographic research and is based on the analysis of the notion of Anthropophagy throughout Oswald's works until its delimitation as a philosophical perspective. The results point to the potency of Anthropophagy as a critical stance of Western thought and to the need for further insights into its philosophical nature, considering its counter-hegemonic meaning.

La presente investigación se centra en la noción de Antropofagia desarrollada por Oswald de Andrade a partir del Manifiesto Antropófago y los ensayos, tesis, artículos y entrevistas en los que vuelve sobre el tema, durante sus últimos años de vida. En cuanto a una definición de Antropofagia, es posible verificar que existen varios significados vinculados a ella, entre los cuales inferimos al menos tres connotaciones efectivas: Antropofagia ritual, cultural y filosófica. Es común observar en los escritos de Oswald y de otros autores que discutieron la Antropofagia la pretensión de que pueda ocupar un lugar de protagonismo teórico y que pueda constituir un tipo de abordaje capaz de pensar críticamente diferentes aspectos de la sociedad brasileña. En este sentido, la investigación pretende esclarecer si la afirmación de Oswald puede llevarse a cabo y, avanzando en el campo de la Antropofagia filosófica, verifica las posibilidades de utilizarla como un enfoque capaz de establecer lecturas sobre los acontecimientos contemporáneos y producir conocimientos que tengan como fundamento la perspectiva crítica de las desigualdades sociales. El trabajo parte de una investigación bibliográfica y parte del análisis de la noción de Antropofagia a lo largo de la obra de Oswald hasta su delimitación como perspectiva filosófica. Los resultados apuntan a la potencia de la Antropofagia como postura crítica del pensamiento occidental y a la necesidad de profundizar en su naturaleza filosófica, considerando su sentido contrahegemónico.
Hunger, devouring and the knowledge of the foot: anthropophagy as a possibility of knowledge production and criticism of contemporary inequalities
Hambre, devorar y el saber del pie: la antropofagia como posibilidad de producción de saber y crítica de las desigualdades contemporáneas
Keywords: Antropofagia; Oswald de Andrade; Desigualdades Sociais; Anthropophagy; Social Differences; Diferencias Sociales; CIENCIAS HUMANAS